2006
DOI: 10.1002/sim.2750
|View full text |Cite
|
Sign up to set email alerts
|

A statistical comparison of different family history scores

Abstract: Family history (FH) scores are used for estimating the familial risk (FR), i.e. the level of risk for a particular disease among members of that family. An FH score is created from reports about the disease status of the relatives in each family. The most commonly used score is the dichotomous score (positive when at least one relative is affected), which does not consider the family size, number of affected relatives nor each relative's risk factor profile. Authors have proposed many other FH scores that over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…10,11 Second, we applied a proportional FH score approach to classify the risk categories of family history of liver cancer, taking into consideration family size and number of affected first-degree relatives in our study population. By a statistical comparison of different FH scores (Proportion, SR, Reed, Williams, Schwartz and Silberberg scores), Murad et al 59 have found surprisingly little difference in the performance of various scores and strongly recommended the usage of the simpler proportion FH score. The internal consistency of findings in both men and women and the "dose-response" of risk with increasing FH score lend credence to our findings.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 Second, we applied a proportional FH score approach to classify the risk categories of family history of liver cancer, taking into consideration family size and number of affected first-degree relatives in our study population. By a statistical comparison of different FH scores (Proportion, SR, Reed, Williams, Schwartz and Silberberg scores), Murad et al 59 have found surprisingly little difference in the performance of various scores and strongly recommended the usage of the simpler proportion FH score. The internal consistency of findings in both men and women and the "dose-response" of risk with increasing FH score lend credence to our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Information about incidence of CVD in the participant's first-and second-degree relatives was obtained from parents in an interview. A family history proportion score was calculated for each person to assess familial risk of developing CVD (Murad, Kalter-Leibovici, Chetrit, & Freedman, 2007).…”
Section: Socio-economic Statusmentioning
confidence: 99%
“…Combining these factors to determine risk presents a challenge. Current methodologies to assess familial risk for common chronic diseases vary from basic dichotomous categorizations (positive/negative) to risk scores developed through refined statistical techniques (59). Another approach is to stratify the risk into a few categories (e.g., average, moderate, high) according to the number of relatives affected, relatives' ages at diagnosis, and the closeness of the biological relationship (87).…”
Section: Wwwannualreviewsorg • Family History In Public Health Pracmentioning
confidence: 99%